Aerosol optical properties of size segregated aerosol particles and radiative forcing over Pokhara valley - Regmi, Jeevn; Poudyal, Khem N; Pokhrel, Amod; Barinelli, Anthony; Aryal, Rudra (Himalayan Physics, 2019)
The AERONET data from sun/sky radiometer over Pokhara (2017) was analyzed to observe aerosol optical depth (AOD) of size segregated particles and radiative forcing. Fine mode particles have over seventy percent of contribution to AOD in all months with the maximum, ninety-four percent, on November and February, and minimum on July, seventy-nine percent. The monthly mean top of atmosphere (TOA) forcing are negative −23.225 ± 4.71 Wm−2 in March, −28.958 ± 4.71 Wm−2 in April and −19.616 ± 4.71 Wm−2 in May. The negative value of TOA during all the months in pre-monsoon season indicates net cooling. Whereas surface forcing (BOA forcing) was found to be positive with a maximum value of 111.18 ± 27.63 Wm−2 during April and a minimum of 56.22 ± 27.63 Wm−2 during May. The resultant atmospheric forcing is the absorption due to aerosols within the atmosphere and found to be +267.57 Wm−2 during April and +228.55 Wm−2 during May; indicating significant heating of the atmosphere.